Disease Management Project Breast Cancer in Hesse – 5-Year Survival Data - Jackisch, C.; Funk, A.; König, K.; Lubbe, D.; Misselwitz, B.; Wagner, U. (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: The Disease Management Project Breast Cancer (DMP Breast Cancer) was first launched in Hesse in 2004. The project is supported by the health insurance companies in Hesse and the Professional Association of Gynaecologists in Hesse. The aim is to offer structured treatment programmes to all women diagnosed with breast cancer in Hesse by creating intersectoral cooperations between coordinating clinics, associated hospitals and gynaecologists in private practice who registered in the DMP programme.Method: Between 1 January 2005 and 30 June 2011, 13 973 women were enrolled in the DMP programme.Results: After data cleansing, survival rates were calculated for a total of 11 214 women. The 5-year overall survival (OS) rate was 86.3 %; survival rates according to tumour stage on presentation were 92.2 % (pT1) and 82.3 % (pT2), respectively. The impact of steroid hormone receptor status on survival (87.8 % for receptor-positive cancers vs. 78.9 % for receptor-negative cancers) and of age at first diagnosis on survival (≤ 35 years = 91 %) were calculated.Conclusion: The project showed that intersectoral cooperation led to significant improvements in the quality of treatment over time, as measured by quality indicators and outcomes after treatment.
Keywords: breast cancer; disease management programme; quality assurance; survival; network